DISMISSAL (IMPEACHMENT) OF THE PRESIDENT AND / OR VICE PRESIDENT ACCORDING TO THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Fahmi Ibrahim; La Ode Husen; Askari Razak (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal